Advice from local/site evaluators: How to manage “up” within a large‐scale initiative - Hwalek, Melanie; Honoré, Matt; Brown, Shavonnea (New directions for evaluation, 2022)
BUilding Infrastructure Leading to Diversity (BUILD), an initiative of the National Institutes of Health (NIH), provides grants to undergraduate institutions to implement and study innovative approaches to engaging and retaining students from diverse backgrounds in biomedical research. The NIH awarded BUILD grants to 10 higher education institutions in multiple states, including funding for local evaluations. This chapter presents findings from an online survey and interviews with 15 local evaluators from nine of the 10 BUILD sites. Participants shared their perspectives on the role of professional local evaluators in national evaluations, ideal national–local multisite evaluation partnerships, and the ways that funders can support these partnerships to maximize impact. They argued for customized technical assistance and other support for local evaluations; the importance of including local results in national evaluation findings; the value of local evaluators’ subject‐matter expertise; and the potential for funders to act as central organizing entities in national–local evaluation partnerships.